The development of informational technology for analysis of different density particles moving in sprue-feed systems - O. I. Chichko; S. G. Lihouzov; V. F. Sobolev (Литьë и металлургия)
Computer method of modelling of the particles of different densit moving in the high-speed field of melt flows in the model three-dimensional object ‘"Stand- pipe -slag catcher — mould*' is offered. There are presented the results of calculations of dispensing of different densit slag particles proportion, localizing in curtain conditions in the area of stand-pipe, slag catcher and mould.